Preparing Social Work Students for Interprofessional Team Practice in Health-Care Settings . (July 2019) - Delavega, Elena; Neely-Barnes, Susan L.; Elswick, Susan Elizabeth; Taylor, Laura C.; Pettet, Fawn Lindsey; Landry, Margaret A.
Purpose: This study presents the results of a workforce development initiative focused on preparing master's-level social work students to work in interprofessional settings and integrated care. The study examines both trainees' changes in interprofessional skills and attitudes as well as if there were differences in trainee experiences across race and gender. Method: Ninety-nine trainees participated in a training program and completed pre- and posttest measures on attitudes toward interdisciplinary teams and team skills. The team used multivariate analysis of variance (MANOVA) to examine the change in means and interaction effects. Results: Findings suggest that the training helps trainees acquire interdisciplinary team skills. However, results on attitudes toward interdisciplinary teams varied based on race and gender of the trainees. Discussion: Results suggest that there continue to be disparities in the training experiences of social work trainees around race and gender. Future research needs to continue to focus on this issue.